تيمة اللاجئ في رواية "ربيع كورونا" "لأحمد الهادي الرشراش" - فاطمة بوعلي (My University, 2026)
Abstract: This research examines the theme of asylum as one of the most prominent humanitarian issues reflecting human suffering caused by wars, crises, and disturbances.It explores the resulting feelings of alienation and the loss of security and stability.The study addresses the concept of asylum ans its relationship with closely related terms and concepts. Furthermore, the research analyses the novel"Corona Spring"(Rabi’al-Corona) by Ahmed Al-Hadi Rashrash, which portrays the suffering of refugees amidst the COVID-19 pandemic and the fear, isolation, and turmoil it imposed. The Study highlights the characters’ persistence in holding onto hope and their continuous quest for safety ans stability despite harsh conditions. Ultimately, it demonstrates that hope remains present even in the most difficult ordeals, and that humans remain steadfast in their dream of a new beginning that is more secure and stable ---------------------- ملخص يعالج هذا البحث موضوع تيمة اللجوء باعتبارها من أبرز القضايا الإنسانية التي تعكس معاناة الإنسان بسبب ما يتعرض إليه من حروب وأزمات وكذلك الاضطرابات، وما ينتج عنها من شعور بالغربة وفقدان الأمان والاستقرار، كما تم التطرق إلى مفهوم اللجوء وعلاقاه ببعض المصطلحات والمفاهيم القريبة منه. ثم تم الانتقال إلى رواية"ربيع كورونا" "لأحمد رشراش" التي جسدت لنا معاناة اللاجئ في ظل جائحة كورونا وما فرضته من خوف وعزلة واضطراب، مع إظهار تمسك الشخصيات بالأمل وسعيها المستمر للبحث عن الأمان والاستقرار رغم الظروف القاسية لتبين أن الأمل يبقى حاصلا حتى في أصعب المحن، وأن الإنسان يظل متمسكا بحلم بداية جديدة أكثر أمانا واستقرارا. ------------------ Résumé: Cette recherche traite la thématique de l’asile en tant que l’une des questions humanitaires les plus marquantes, reflétant la souffrance humaine causée par les guerres, les crises et les troubles. Elle analyse également le sentiment d’aliénation ainsi que la perte de sécurité et de stabilité qui en résultent. L’étude aborde en outre le concept de l’asile et ses liens avec certaines notions connexes. Elle s’intéresse ensuite au roman Le Printemps de Corona d’Ahmed Errachrach, qui illustre la souffrance du réfugié durant la pandémie de la COVID-19, ainsi que les sentiments de peur, d’isolement et de bouleversement qu’elle a engendrés. Tout en mettant en évidence l’attachement des personnages à l’espoir et leur quête permanente de sécurité et de stabilité malgré les conditions difficiles, l’étude montre que l’espoir demeure vivant même dans les moments les plus éprouvants, et que l’être humain reste attaché au rêve d’un nouveau départ, plus sûr et plus stable.
Keywords: refugee theme; asylum; human; suffeeing; COVID19pandemic; تيمة اللاجئ، اللجوء، المعاناة الإنسانية، جائحة كورونا.; Thématique du réfugié; asile; souffrance humaine; pandémie de la COVID-19